A TRANSGRESSÃO SERTANEJA DO GÊNERO RELATÓRIO: Revelação do escritor no texto do prefeito Graciliano Ramos - Jaconi, Sônia Maria Ribeiro (2012)
This thesis aims to investigate the genre report, in order to know its constituent characteristics, situational context and the socio-communicative role that it plays among its speech community. The object of this research are the public reports written by the mayor Gracialiano Ramos, in the years 1929 and 1930, and sent to the governor of Alagoas State. These documents have achieved great impact at the time, due to the ironic and daring tone present in the texts, indicating a violation of the genre of report writing. For the analysis, it were defined the figures of rhetoric according to Quintiliano de Calahorra, and their incidence in these texts, paying attention to the transgressions committed by the manager-writer. To achieve our goals, the methodology used was the analysis of standardized text and textualization, proposed by Bhatia, with the analysis of expression, as proposed by Laurence Bardin.